2020
DOI: 10.1186/s12879-020-05283-1
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis active case-finding interventions and approaches for prisoners in sub-Saharan Africa: a systematic scoping review

Abstract: Background: In sub-Saharan Africa (SSA), most prisons are overcrowded with poor ventilation and put prisoners disproportionally at risk of exposure to Mycobacterium tuberculosis (TB) and developing TB infection but are mostly missed due to poor access to healthcare. Active case-finding (ACF) of TB in prisons facilitates early diagnosis and treatment of inmates and prevent the spread. We explored literature and described evidence on TB ACF interventions and approaches for prisoners in SSA prisons. Methods: Guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…The increased TB prevalence in the prisons compared to the outside communities is demonstrated in this project and other related studies in Nigerian prisons [12][13][14]. It is crucial that while efforts are being made to implement the strategies outlined by the United Nations' office on crime and drugs to decongest the prisons, 23 routine TB ACF approaches, including entry and routine mass screening, [15] are implemented in Nigerian Prisons. It is noteworthy that all inmates that opted out of the TB screening were on death row.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The increased TB prevalence in the prisons compared to the outside communities is demonstrated in this project and other related studies in Nigerian prisons [12][13][14]. It is crucial that while efforts are being made to implement the strategies outlined by the United Nations' office on crime and drugs to decongest the prisons, 23 routine TB ACF approaches, including entry and routine mass screening, [15] are implemented in Nigerian Prisons. It is noteworthy that all inmates that opted out of the TB screening were on death row.…”
Section: Discussionmentioning
confidence: 81%
“…Due to the lack of evidence on TB ACF in most sub-Saharan African (SSA) countries, a recent systematic review has called for increased ACF interventions in SSA prisons, particularly countries included in the three high-burden country lists for TB, TB/HIV, and MDR-TB [15]. Nigeria's inclusion in the three high-burden lists justified the ACF intervention in Nigeria Prisons.…”
Section: Introductionmentioning
confidence: 99%
“…Geographically, most people who developed TB are in South-East Asia (44%), Africa (25%) and the Western Pacific (18%) [9]. It is estimated that 94% of all TB infections and deaths occur appropriately in low-and middle-income countries, including sub-Saharan Africa (SSA) [10]. An observational study suggested that individuals with latent or active TB were more susceptible to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection [11].…”
Section: Introductionmentioning
confidence: 99%
“…Prison conditions have been reported to increase the risk of respiratory diseases such as tuberculosis (TB) [ 3 , 5 , 5 , 6 ], but there is limited data on the burden of non-communicable respiratory diseases among inmates. Poor indoor air quality in prisons has been documented, and this potentially increases the risk of NCD such as asthma, chronic obstructive pulmonary disease, lung cancer and low lung function [ 2 , 7 9 ]. High frequency of indoor tobacco smoking among inmates coupled with poor ventilation and limited opportunities for outdoor activities also potentially increase the risk of exposure to indoor air pollution and its adverse health outcomes [ 2 , 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a Nigerian prison, frequent cough and catarrh was reported in nearly 70% of the inmates and there are currently no reports of lung function measures among inmates from Nigeria [ 3 ]. However, spirometry diagnosed chronic obstructive pulmonary disease (COPD) was reported in up to 20% of inmates in Bolvadin closed and open prison, in Turkey [ 7 ]. To drive policy for improvement in prison conditions, substantial evidence of adverse impact of the harsh conditions is needed.…”
Section: Introductionmentioning
confidence: 99%